1990
DOI: 10.1007/bf01648242
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in drug addicts

Abstract: We studied trace elements (zinc, copper, magnesium, iron, and lithium) by atomic absorption spectrophotometry in the plasma and erythrocytes of 120 subjects: 20 healthy controls and 100 parenteral drug addicts (69 heroin and 31 heroin + other drugs). Plasma Zn and intraerythrocytic Zn and Fe were decreased, whereas plasma and intraerythrocytic Cu were significantly increased in the group of drug addicts with respect to the healthy controls. Moreover, a period of abstinence longer than 10 days was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Low zinc serum concentrations were reported in heroin consumers upon admission for treatment, with a slight tendency to increase during detoxification, yet not reaching the levels in controls [ 44 ]. In patients diagnosed with heroin addiction, zinc deficit appears to be correlated with the abuse period in case of heroin addiction [ 45 ] and low zinc plasma is accompanied by low intraerythrocytic zinc and by increased plasma and intraerythrocytic copper [ 46 ]. In case drug-free patients with heroin-addiction documented in the past, zinc concentration in the cerebrospinal fluid (CSF) of is lower than in controls, but generally within normal limits [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Low zinc serum concentrations were reported in heroin consumers upon admission for treatment, with a slight tendency to increase during detoxification, yet not reaching the levels in controls [ 44 ]. In patients diagnosed with heroin addiction, zinc deficit appears to be correlated with the abuse period in case of heroin addiction [ 45 ] and low zinc plasma is accompanied by low intraerythrocytic zinc and by increased plasma and intraerythrocytic copper [ 46 ]. In case drug-free patients with heroin-addiction documented in the past, zinc concentration in the cerebrospinal fluid (CSF) of is lower than in controls, but generally within normal limits [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…They reported that the concentrations of Fe, Ca, P, S, Cl, K, Mn, and Zn from the blood samples of heroin addicts is lower, while Cu and Br content was higher with respect to the control group. Martinez et al [2] reported this drop in Fe and Zn concentration, and according to their studies there was no significant difference in magnesium levels between the drug addicts and healthy subjects. They studied trace elements by atomic absorption spectrophotometry in the plasma and erythrocytes of 120 subjects: 20 healthy control subjects and 100 drug addicts (69 heroin and 31 heroin other drugs).…”
Section: A Nail Spectrummentioning
confidence: 92%
“…Traditional samples such as urine, blood [1,2], and more recently saliva and sweat are of basic significance in toxicological analysis for different purposes at times when only recent exposure to drugs is investigated [3]. The changes in molecular compositions and compounds in these samples, due to drug abuse, are temporary and can be masked by with special beverages that reduce the accuracy of these tests.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have tested the hypothesis that illicit drug use and lifestyle impair serum trace element status. In an earlier study, it was reported that plasma Zn and Fe were decreased, whereas plasma Cu was significantly increased in drug addicts compared to the healthy controls [17].…”
Section: Introductionmentioning
confidence: 98%